Playing Tetris Lets You Rate Odors as Less Intense - Schadll, Stephan; Rodriguez-Raecke, Rea; Heim, Lennart; Freiherr, Jessica (Frontiers in Psychology, 2021)
Overweight and obesity are considered a huge problem in modern societies. Previous studies have shown that people who are regularly distracted by playing videogames or watching TV while eating are more likely to be overweight and that the number of people that are gaming worldwide is rising. Further, it has been established that both, watching TV or playing video games lead to an increased snack intake and a lower rating of perceived taste intensity. Since flavor perception is accomplished not only by the sense of taste but also the sense of smell, we investigated the influence of cognitive load created by playing a video game on odor intensity perception. The participants played a low or high difficulty version of Tetris while presented with odors of food and non-food items. A higher skin conductance response (SCR) along with a decrease in task performance verified that the higher difficulty level leads to a higher cognitive load. Our behavioral data indicates a significant decrease in intensity estimates of food odors and non-food odors during the high compared to low cognitive load condition. We conclude that odor intensity estimation is influenced by real-life cognitive tasks which might in turn lead to overeating while distracted.